Exploring international clinical education in US-based programs: identifying common practices and modifying an existing conceptual model of international service-learning. (February 2014) - Pechak, Celia M.; Black, Jill D.
Abstract Background: Increasingly physical therapist students complete part of their clinical training outside of their home country. This trend is understudied. The purposes of this study were to: (1) explore, in depth, various international clinical education (ICE) programs; and (2) determine whether the Conceptual Model of Optimal International Service-Learning (ISL) could be applied or adapted to represent ICE. Methods: Qualitative content analysis was used to analyze ICE programs and consider modification of an existing ISL conceptual model for ICE. Fifteen faculty in the United States currently involved in ICE were interviewed. The interview transcriptions were systematically analyzed by two researchers. Results: Three models of ICE practices emerged: (1) a traditional clinical education model where local clinical instructors (CIs) focus on the development of clinical skills; (2) a global health model where US-based CIs provide the supervision in the international setting, and learning outcomes emphasized global health and cultural competency; and (3) an ICE/ISL hybrid where US-based CIs supervise the students, and the foci includes community service. Additionally the data supported revising the ISL model's essential core conditions, components and consequence for ICE. Conclusions: The ICE conceptual model may provide a useful framework for future ICE program development and research.